Carbamazepine and carbamazepine-epoxide concentrations in mothers, colostrum, and breastfed newborns: Comparison with concentrations determined during delivery and in the mature milk period - Kacirova, Ivana; Grundmann, Milan; Brozmanova, Hana (Biomedicine & pharmacotherapy, 2022)
OBJECTIVE: To obtain information on the transport of carbamazepine and its active metabolite carbamazepine-epoxide from mother to colostrum and breastfed newborns. METHODS: In this cohort study, carbamazepine and carbamazepine-epoxide concentrations in maternal serum (162 women), milk (i.e., colostrum) and breastfed newborn serum were analysed between the 1st and 5th days after delivery from November 1990 to February 2021. The measured concentrations were compared with the delivery and mature milk periods. The effect of the combination with both enzyme-inducing antiseizure medication and valproic acid was also evaluated. RESULTS: Carbamazepine concentrations varied from 1.0 to 11.2 mg/L (epoxide 0.3-4.4 mg/L) in maternal serum, from 0.5 to 6.8 mg/L (epoxide 0.3-2.4 mg/L) in milk and from 0.5 to 4.7 mg/L (epoxide 0.3-1.7 mg/L) in newborn serum. The median milk/maternal serum concentration ratio of carbamazepine was 0.45 (epoxide 0.71), the median newborn/maternal serum concentration ratio of carbamazepine was 0.20 (epoxide 0.41), and the median newborn serum/milk concentration ratio of carbamazepine was 0.38 (epoxide 0.50). A highly significant correlation was found between the milk and maternal serum concentrations of both carbamazepine and carbamazepine-epoxide and between the milk and newborn serum concentrations of carbamazepine. CONCLUSIONS: In the serum of breastfed newborns, only one concentration of carbamazepine reached the reference range used for the general epileptic population, and more than half was below the lower limit of quantification. Routine monitoring of serum carbamazepine concentrations is not required in breastfed newborns. However, observation of newborns is desirable, and if signs of potential adverse reactions are noted, the serum concentrations in newborns should be measured.
Keywords: karbamazepin; Cohort Studies; Carbamazepine; Female; Epoxy Compounds; benzodiazepiny; Colostrum; novorozenec; Benzodiazepines; kolostrum; epoxidové sloučeniny; těhotenství; Breast Feeding; kohortové studie; antikonvulziva; ženské pohlaví; kojení; Mothers; Pregnancy; Anticonvulsants; Milk, Human; Concentrations; lidé; Humans; mateřské mléko; Therapeutic drug monitoring; Carbamazepine-epoxide; matky; Infant, Newborn